2022
DOI: 10.1021/acs.analchem.2c02416
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Heterogeneous Circulating Tumor Cells in Colorectal Cancer Patients on an Immunomagnetic and Anti-Nonspecific Adsorption Platform

Abstract: Circulating tumor cells (CTC) have been represented by different phenotypes due to the epithelial−mesenchymal transition (EMT), which are epithelial CTC (E-CTC), mesenchymal CTC (M-CTC), and mixed (epithelial, mesenchymal) CTC (EM-CTC). Limited work has systematically discussed the associations of CTC number, especially proportions of E-CTC, M-CTC, and EM-CTC in total CTC, with colorectal cancer (CRC) progressions via a simple method with high performances. To achieve this goal, this paper presents the fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Based on the immunomagnetic platform Fe 3 O 4 @SiO 2 @PTMAO@aptamer, Li et al detected the number of epithelial CTC (E-CTC), stromal CTC (M-CTC) and mixed (epithelial and stromal) CTC (EM-CTC) in blood samples of patients with colorectal cancer, and analyzed the correlation between different phenotypes of CTCs and clinical information of CRC patients. 28 The changes of the proportion of heterogeneous CTC in 40 patients with different stages of colorectal cancer before and after operation showed that the number and proportion of E-CTC or M-CTC was significantly lower than that of EM-CTC and M-CTC. This was positively correlated with the metastasis of colorectal cancer and the effect of operation and chemotherapy in patients with CRC.…”
Section: Disease Detection and Prognosis Evaluationmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on the immunomagnetic platform Fe 3 O 4 @SiO 2 @PTMAO@aptamer, Li et al detected the number of epithelial CTC (E-CTC), stromal CTC (M-CTC) and mixed (epithelial and stromal) CTC (EM-CTC) in blood samples of patients with colorectal cancer, and analyzed the correlation between different phenotypes of CTCs and clinical information of CRC patients. 28 The changes of the proportion of heterogeneous CTC in 40 patients with different stages of colorectal cancer before and after operation showed that the number and proportion of E-CTC or M-CTC was significantly lower than that of EM-CTC and M-CTC. This was positively correlated with the metastasis of colorectal cancer and the effect of operation and chemotherapy in patients with CRC.…”
Section: Disease Detection and Prognosis Evaluationmentioning
confidence: 94%
“…70 Li et al designed a new type of anti-non-specific adsorption immunomagnetic platform Fe 3 O 4 @SiO 2 @PTMAO@aptamer, which can efficiently capture different phenotypes of CTCs in 10 min, and briefly analyzed the relationship between different phenotypes of CTCs and the progression, diagnosis, surgery and chemotherapy of colorectal cancer (CRC) patients. 28 In addition, the team designed double aptamer (EpCAM and PTK7)-modified immunomagnetic Fe 3 O 4 particles for the effective capture and downstream analysis of heterogeneous CTCs in patients with gastric cancer (Fig. 5C ).…”
Section: Biological Properties For Isolationmentioning
confidence: 99%
“…Circulating tumor cells (CTCs) are the “seeds” of malignant tumor metastasis that detach from the primary tumor, breach the basement membrane, and enter the bloodstream or lymphatic fluid. , They are widely observed in various types of tumors. Therefore, research on the nondestructive capture of CTCs holds clinical value in minimally invasive tumor diagnosis, disease monitoring, prognosis assessment, drug guidance, and even drug efficacy evaluation. Among these, nondestructive CTC capture is the most critical prerequisite. Currently, CTC capture techniques have been extensively studied. Some aim to utilize CTC-specific membrane protein biomarkers, while others aim to exploit the unique physical properties of CTCs, such as membrane potential. , However, unfortunately, strategies for CTC capture that maintain high specificity, sensitivity, and universality remain limited . Specifically, membrane protein biomarkers undoubtedly provide targets for highly specific CTC capture.…”
Section: Introductionmentioning
confidence: 99%
“…7−9 Currently, CTC capture techniques have been extensively studied. 10−14 Some aim to utilize CTC-specific membrane protein biomarkers, 11 while others aim to exploit the unique physical properties of CTCs, such as membrane potential. 15,16 However, unfortunately, strategies for CTC capture that maintain high specificity, sensitivity, and universality remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…Since the CTCs are from the tumor tissue, they usually carry different characteristics from the blood cells. Various strategies have been applied to enrich the CTCs by using these characteristics, including cell density, size, etc., and those by taking advantage of antibodies, , aptamers, or peptides , to capture the CTCs based on the specific biomarkers on the surface of it. To improve the enrichment performance, microfluidics or functional nanomaterials are especially favored. After the enrichment, immunodetection or gene-related strategies are introduced to identify and analyze the cells further.…”
mentioning
confidence: 99%